FEATURES AND TAX TECHNOLOGIES OF REGISTRATION AND ACCOUNTING OF TAX PAYERS IN UKRAINE - Костишин, Наталія (Modern engineering and innovative technologies, 2024)
The article examines the peculiarities and tax technologies of taxpayer registration depending on the choice of their type of activity. The modern rapid development of economic processes and digitization of all spheres of life brings changes to every lin